(untitled) (Acta Scientiarum. Biological Sciences, 2018)
The Atlantic Forest in the State of Paraíba integrates the Pernambuco Center of Endemism. The present work investigated understory bird communities of three of its remnants using ten mist nets installed at eight different points of the forest understory of each area. We captured 333 birds of 44 species and 19 families. Bird richness and abundance did not differ between the three remnants (KW = 6.08; p = 0.04 and KW = 10.54; p = 0.004). The composition was little similar among them, and each area presented high species diversity and evenness. The most captured species were Arremon taciturnus (n = 40), Chiroxiphia pareola (n = 32) and Conopophaga melanops (n = 28). C. melanops has a local threat status of “vulnerable” and is considered endemic. Endangered and endemic species each represented 15.91% of the captures. Both Reserva Biológica Guaribas areas had the highest number of threatened species, while Reserva Particular do Patrimônio Natural Engenho Gargaú showed the highest number of endemic and understory insectivorous species, which indicates a better quality status in comparison to the other two. These results show the importance of the remnants to bird conservation in Northeastern Brazil.